Development of Website-Based Animated Learning Media for Instilling Honesty, Discipline, and Responsibility in Second-Grade Elementary School Students - Nisa Sugiharti; Ani Nur Aeni; Farisha Fatihaturohmah; Hanifa Isti (Cahaya Ilmu Cendekia Publisher, 2026)
website-based animated video learning media for grade II elementary school students and to evaluate its effectiveness in enhancing students’ understanding and internalization of moral values. Methodology: This study employed the Research and Development (R&D) method using the ADDIE model. The participants were 29 second-grade students and one Islamic Religious Education teacher at SDN Gudang Kopi 1. Data collection instruments included interviews, observations, documentation, pre-tests, and post-tests. Canva, CapCut, Whisk AI, and Wordwall were used for media development. Main Findings: The developed website-based interactive animation video media achieved a material expert validation score of 97.5% and a media expert validation score of 100%, indicating very high feasibility. Students’ mean scores increased from 75 in the pre-test to 88 in the post-test, with an N-Gain score of 0.52 (moderate category). Positive improvements were observed in students’ discipline, politeness, responsibility, and mutual assistance. Novelty/Originality of this study: This study introduces a website-based learning platform that integrates animated storytelling, educational games, and moral decision-making activities into a single instructional medium. The study extends existing research on animation-based learning by combining interactive multimedia features to support both moral understanding and the application of moral values among elementary school students.